2013
DOI: 10.1177/0300060513487625
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme insertion/deletion gene polymorphism and risk of intracranial aneurysm in a Chinese population

Abstract: The relationship between angiotensin-converting enzyme (ACE) insertion/deletion (I/D) gene polymorphisms and intracranial aneurysm (IA) has been studied in Caucasian and Japanese populations. The present study aimed to investigate this association in a Chinese population. Methods: Patients with confirmed IA and age-and sex-matched control subjects without evidence of IA were enrolled. ACE I/D gene polymorphisms were analysed using polymerase chain reactionrestriction fragment length polymorphism. Results: A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Polymorphisms within the kallikrein gene cluster are associated with intracranial aneurysms suggesting that the kallikreins are important candidate genes for intracranial aneurysms [ 22 ]. Evidence from a case-control study suggested that the angiotensin-converting enzyme DD genotype might be a protective factor for intracranial aneurysms in a Chinese population [ 23 ]. Evidence from a meta-analysis of case-control studies also suggested that there was a close relationship between angiotensin-converting enzyme I/D polymorphism and intracranial aneurysms risk [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms within the kallikrein gene cluster are associated with intracranial aneurysms suggesting that the kallikreins are important candidate genes for intracranial aneurysms [ 22 ]. Evidence from a case-control study suggested that the angiotensin-converting enzyme DD genotype might be a protective factor for intracranial aneurysms in a Chinese population [ 23 ]. Evidence from a meta-analysis of case-control studies also suggested that there was a close relationship between angiotensin-converting enzyme I/D polymorphism and intracranial aneurysms risk [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that patients with LVH tend to have higher rates of DD genotype. 26 So, the LVH is also a common complication in coronary disease. Altogether, comparison of the distribution of patients' characteristics according to the genotypes of the ACE I/D polymorphism showed no significant differences in all characteristics except for the percentage of patients' survival after SCA and patients' death by SCA, which is an interesting result.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood was collected and DNA was extracted from leukocytes as described earlier. 26 Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was used to analyze ACE I/D gene polymorphisms.…”
Section: The Ace I/d Genotypementioning
confidence: 99%
“…In addition, Liu et al (17) reported that no statistically significant differences were identified between genotypes in patients with IA, when stratified by the site, shape, size and Fisher Grade of aneurysms (17). In future studies, greater focus on clinical characteristics, such as gender, alcohol consumption, smoking, family history, and site, shape, size and Fisher Grade of IA should be taken into consideration to provide a more powerful analytical framework.…”
Section: Codominant Model -------------------------------------------mentioning
confidence: 99%
“…Certain previous studies investigated the influence of ACE I/D gene polymorphisms on IA susceptibility (17)(18)(19)(20)(21)(22)(23); however, the results of these studies remain inconsistent. As a single study might not be powered to demonstrate the overall effects, Association between angiotensin-converting enzyme insertion/deletion polymorphisms and intracranial aneurysm susceptibility: A meta-analysis a meta-analysis using currently available data was performed in the present study to detect the potential association of ACE I/D gene polymorphisms on IA risk.…”
Section: Introductionmentioning
confidence: 99%